2022
DOI: 10.1111/jmwh.13459
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Prenatal Care: An Integrative Review

Abstract: Introduction Prenatal care (PNC) is a core element of preventive care and is vital in identifying and managing conditions that can put the pregnant person and the fetus at risk. National and international guidelines differ in what is considered adequate or quality PNC. Indices of care adequacy rely only on number of attended PNC visits without regard to factors that affect a patient's ability to obtain care or the quality of the care received. This integrative review explored stakeholders’ perceptions of adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Breman et al, 26 who examined visit schedule changes from the client's perspective, noted that these alterations contributed to clients’ impressions they were receiving subpar care. There is as yet no strong evidence to support the usual schedule of 14 to 15 prenatal visits versus an abbreviated schedule 27,28 . Hence, alternative visit schedules, if adopted, should be thoroughly explained to clients and appropriate reassurance provided, with clear advice on and support for additional contacts upon request.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breman et al, 26 who examined visit schedule changes from the client's perspective, noted that these alterations contributed to clients’ impressions they were receiving subpar care. There is as yet no strong evidence to support the usual schedule of 14 to 15 prenatal visits versus an abbreviated schedule 27,28 . Hence, alternative visit schedules, if adopted, should be thoroughly explained to clients and appropriate reassurance provided, with clear advice on and support for additional contacts upon request.…”
Section: Discussionmentioning
confidence: 99%
“…There is as yet no strong evidence to support the usual schedule of 14 to 15 prenatal visits versus an abbreviated schedule. 27,28 Hence, alternative visit schedules, if adopted, should be thoroughly explained to clients and appropriate reassurance provided, with clear advice on and support for additional contacts upon request. Although research suggests telehealth prenatal visits are acceptable to clients and providers, 29 there is a need to determine which midwifery visit types can be safely and appropriately conducted via telehealth and to advocate for equitable reimbursement for telehealth visits.…”
Section: Implications For Practice Advocacy and Researchmentioning
confidence: 99%
“…Despite the focus on the quantity of visits, debate also exists about what constitutes adequate and quality prenatal care. Michel and Fontenot (2023) proposed that the current prenatal care structure based on the number of in-person visits without discussions of quality of care does not address barriers to access related to socioeconomic, employment, or other circumstances. New, hybrid, prenatal care models have the potential to increase uptake, but they also need to address other barriers to access, including internet and equipment availability.…”
Section: Telehealth During Covid-19mentioning
confidence: 99%
“…This highlights the importance of prenatal and postnatal care for hypertension during pregnancy. [ 11 ] A separate study revealed that during the latter stages of pregnancy, there exists an inverse relationship between the severity of depression and the duration of walking as a physical activity. Additionally, walking was found to have a positive correlation with anxiety levels.…”
Section: Introductionmentioning
confidence: 99%